2021
DOI: 10.3390/en14238139
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture as a Prerequisite for Knowledge Transfer among IT Professionals: The Case of Energy Companies

Abstract: The energy sector is the epitome of Industry 4.0; therefore, it should be developed in line with the Industry 4.0 implementation framework and be managed according to the guidelines dedicated to knowledge-based enterprises. Under this model of evolution, the layers surrounding the technological aspects are first, knowledge management (in particular, its transfer), and then people, and culture. This study addresses two of the three identified levels by attempting to verify the organizational culture that suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 152 publications
(225 reference statements)
0
5
0
Order By: Relevance
“…K.M. encompasses not only the processes and tools for managing knowledge but also knowledge diffusion, which deals with how an individual entity applies the information it possesses throughout the entire organization [26,58].…”
Section: Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…K.M. encompasses not only the processes and tools for managing knowledge but also knowledge diffusion, which deals with how an individual entity applies the information it possesses throughout the entire organization [26,58].…”
Section: Knowledge Managementmentioning
confidence: 99%
“…plays a crucial role in supporting strategic thinking and decision-making by facilitating learning, establishing connections and networks, enabling knowledge flows, and generating knowledge, ideas, and visions. Pietruszka-Ortyl et al [58] identified a strong association between the use of modern technologies for K.M. and the application of S.F.…”
Section: The Moderating Role Of Knowledge Management On the Relations...mentioning
confidence: 99%
“…A merger is a basic form of merging two separate enterprises into one entity. The distinguishing feature of a merger is that, as a rule, it takes place as a result of the concerted and free action of partners [42].…”
Section: Theoretical Approaches To Mergers and Acquisitions As A Mani...mentioning
confidence: 99%
“…Future research should be conducted with a larger sample sizes and probability sampling to ensure rigor in the study. (2) Growth organizational culture is one type of the various types of culture, and more research is needed to find out other culture types how to effect organizational performance. (3) The variable endogeneity is not well solved, which affects the generalization of the conclusion.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…Organizations must increasingly maintain a culture to gain a competitive advantage. Research found that innovative culture has a significant positive impact on knowledge transfer performance, but whether supportive culture has an impact on knowledge transfer performance has not been confirmed [2,3]. One study showed innovative culture and supportive culture has a positive impact on organizational innovation performance, while bureaucratic culture has no significant effect on organizational innovation performance [4].…”
Section: Introductionmentioning
confidence: 99%